Optimization of Process Parameters during TIG Welding of 304L Stainless Steel with and without Flux - Suraj, Md; Tripathy, S.; Pallavi Senapati, N. (International Journal of Engineering and Technology, 2018)
The aim of this experimental study is to investigate the welding performance of 304L stainless steel by tungsten inert gas (TIG) welding process. SiO2 and CdCl2 were used as fluxes for welding using activated flux (A-TIG) and the influence of machining factors on the welding responses of 304L stainless steel were compared and studied. The experimental design was carried out using Taguchiâ€™s technique where L27 orthogonal array was used for welding. Multi-objective optimization was carried out using PCA based TOPSIS method to find the optimal sample among the entire samples. The optimal sample was found to be SiO2 flux at welding current=160 A, gas flow rate=16l/min and weight of the flux=0.147g.Â